The effect of academic advising on academic performance of university students in Kenyan universities - Muola, James Muthee; Maithya, Redempta; Mwinzi, A.M. (International Association of African Researchers, 2011)
Although academic advising in Kenyan universities exists, no research has been done to find out how it impacts on students’ educational and career goals. This research aimed at establishing the effect of academic advising on academic performance and the influence of year of study and gender on students’ tendency to seek academic advising. The ex-post facto research design was used. A questionnaire was used to collect data. A random sample of 187 (53, 41 and 93 first, second and third year students respectively.) participated in the study. Purposive sampling was used to select Laikipia University College of Egerton University which is one of the seven public universities in Kenya. No significant relationship (r = 0.099) was found between academic advising and academic performance. The findings showed that, first (21%) and second (27%) year students are more likely to seek academic advising than third year students (4%). An equal and low percentage (14%) of male and female students sought academic assistance from their academic mentors. The findings were attributed to the low percentage (11%) of students seeking academic advising and students’ needs at different years of study irrespective of gender. It was recommended that academic advising should actively involve more students
Keywords: Academic performance; Advising; Year of study and gender